Faktor-Faktor yang Mempengaruhi Struktur Modal Perusahaan Pada Perusahaan Manufaktur Go Public di Bursa Efek Jakarta Tahun 2017-2019 - Siti Marlina; Kasiyati Yunita Wulansari (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT UNIVERSITAS GRAHA KARYA MUARA BULIAN, 2021)
The purpose of this study is to find out about the factors that affect the company's capital structure in go public manufacturing companies on the Jakarta stock exchange in 2017-2019. In this study using a quantitative research type. Data analysis tools used multiple regression, T test, F test and determination. The results of the research obtained partial test, it turns out that company size, asset growth, and company profitability have a real effect, in the variables that have the greatest influence is company size of 28.4%, asset growth of 25.3% and profitability of 17.14% which means that managers pay more attention to these three factors in making decisions related to capital structure. simultaneous company size, business risk, asset growth, profitability and capital structure. This shows that in making decisions about the capital structure to be used or applied, the managers of manufacturing companies at the JSE consider company size, business risk, asset growth, profitability and the company's existing ownership structure. The coefficient of determination turns out to be 35%, which means that company size, business risk, asset growth, profitability and company ownership structure jointly affect the capital structure while the remaining 65% is influenced by other factors.